Prenatal exposure to pesticide residues in the diet in association with child autism‐related traits: Results from the EARLI study. Issue 5 (8th March 2022) - Joyce, Emily E.; Chavarro, Jorge E.; Rando, Juliette; Song, Ashley Y.; Croen, Lisa A.; Fallin, M. Daniele; Hertz‐Picciotto, Irva; Schmidt, Rebecca J.; Volk, Heather; Newschaffer, Craig J.; Lyall, Kristen
Abstract: Prior work has suggested associations between prenatal exposure to several classes of pesticides and child autism spectrum disorder (ASD). We examined a previously developed pesticide residue burden score (PRBS) and intake of high pesticide residue foods in association with ASD‐related traits. Participants were drawn from the Early Autism Risk Longitudinal Investigation (EARLI) ( n  = 256), a cohort following mothers who previously had a child with ASD through a subsequent pregnancy and that child's development. ASD‐related traits were captured according to total Social Responsiveness Scale (SRS) scores at age 3 (mean raw total SRS score = 35.8). Dietary intake was assessed through a food frequency questionnaire collected during pregnancy. We also incorporated organic intake and fatty foods in modified versions of the PRBS. Associations between high‐residue fruit and vegetable intake, the overall PRBS and modified versions of it, and SRS scores were assessed using multivariable linear regression. Overall, we did not observe associations between pesticide residues in foods and ASD‐related outcomes, and modified versions of the PRBS yielded similar findings. However, reductions in ASD‐related traits were observed with higher overall fruit and vegetable intake (adjusted estimates for Q4 vs. Q1: β −12.76, 95%CI −27.8, 2.3). Thus, findings from this high familial probability cohort did not suggest relationships between pesticide residues in the diet according to the PRBS and ASD‐related traits. Beneficial effects of fruit and vegetable intake may influence these relationships. Future work should consider fruit and vegetable intake in association with ASD‐related outcomes. Lay Summary: Diet is the main source of exposure to most pesticides in use today. In this study, we examined the relationship between pesticide exposure from residues in the diet during pregnancy and child autism‐related traits. We found that these pesticide residues from the diet were not related to child autism‐related outcomes at age three. However, higher prenatal fruit and vegetable intake was associated with reductions in child autism‐related traits.